Inter-partner Agreement of Condom Use and Sexual Positioning in Male Couples. Issue 2 (12th February 2022) - Walsh, Alison R.; Sullivan, Stephen; Stephenson, Rob
ABSTRACT: Accurate, reliable self-reports of sexual behavior are a crucial component of valid HIV risk-estimation and behavioral intervention evaluation, yet this data's reliability remains understudied. The goal of this study was to describe interpartner agreement on recent receptive anal intercourse (AI) and condomless receptive AI frequencies, among a sample of male couples. We quantified interpartner agreement on self-reported receptive AI and condomless receptive AI (absolute and relative to AI frequency), and position and condom use during a couple's most recent AI, using cross-sectional data from male partners (US, 2016–2017; N = 718 individuals). Proportional and statistical agreement (intraclass correlation coefficients (ICC), kappa (k)) were assessed. Observed agreement for receptive AI frequency was 49.44% (ICC (95% CI): 0.82(0.79, 0.84)) and for relative receptive frequency, 59.05% (ICC: 0.96 (0.85, 0.96). Agreement on condomless receptive AI was 90.21% (ICC: 0.78 (0.75, 0.82), and for relative condomless receptive AI, 91.15% (ICC: 0.80 (0.77, 0.83). Most recent AI position agreement was 89.42% (k (95% CI): 0.84 (0.80, 0.88)), and condom use, 98.89% (k: 0.82 (0.87, 0.98)). Observed agreement was higher among those who reported consistent positioning and condom use. Further research on self-reported sexual behavior data is needed to improve research validity and intervention effectiveness.